The financial impacts of board mechanisms on performance: The case of listed Moroccan banks - El Idrissi, Issam; Alami, Youssef (Goodwood Publishing, 2021)
Purpose: The present study examines the impact of corporate governance mechanisms on listed Moroccan banks' financial performance. Research methodology: This study investigates the relationship between listed banks' governance mechanisms and financial performance in the CSE for six years between 2014-2019. This study employs three performance measures, return on assets, return on equity, and Tobin's Q, to determine bank performance. This research uses the GMM EGLS approach to analyze data. In the first phase of this empirical research, we did use OLS, Fixed Effects, and Radom Effects regressions to show their inefficiency. Results: Our results portray that most board mechanisms have a negative impact on financial performance. In comparison, the audit committee and nomination & remuneration committee have a positive effect on financial performance. Limitations: Many qualitative and quantitative factors could influence financial performance and not only the used variables in this paper. Contribution: This research shows that the dynamic connection between corporate governance and financial performance is robust in the Moroccan banking context. Also, our study has important implications for establishing good corporate governance practices in emerging economies.